Integrasi Angkutan Keretaapi Dengan Bus Damri Di Stasiun Tugu Yogyakarta - Lestari, Sri; Atun, Sri (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Yogi;akarta cihj is one of the tourist cihj and a universihj to11m and a cih; full of culture that hard tobreak, other than within the cih;, as well as tourists from abroad and students wlw want to registersclwols that migrate out of population yogi;aknrtn yogyaknrta with routine e7.1en; Idul Fitri, flockflocked to visit nyeknr fogjaknrtn . One of tile 11zo1ks arf' quite populnr and beazme tlze people's choiceis rail, because beside the railwm; is a mode of mass transit modes of transportation also has someadvantages safe, comfortable, safe and timely when compared with other transportation modes.Yogi;aknrta Tugu station to sen1e several hjpes of rail freight business executives and train withpassengers on auerage each dm; to reach 6.5 t/wusand passengers, especially on big dm;s and weeksand, with the number of passengers, the passengers off the train modes require continued until hereached the final destination, especially passengers wlw headed jogja town with a bus transportationmodes, especially road Oamri. One of tlze expected proficienci; le7.1el in these sulusi overcome theMunicipal Government of Yogi;aknrtn (Yogi;aknrtn Transportation AgenCIJ) with PT. Rnilwm;s andPerum Oamri cooperation provided means of road transport continued until he reached the finaldestination of the integration of rail with bus transportation Oamri.